2005
DOI: 10.1182/blood-2004-04-1473
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment and survival following reduced-intensity allogeneic peripheral blood hematopoietic cell transplantation is affected by CD8+ T-cell dose

Abstract: The influence of graft composition on clinical outcomes after reduced-intensity conditioning is not well-characterized. In this report we prospectively enumerated CD34 ؉ , CD3 ؉ , CD4 ؉ , and CD8 ؉ cell doses in granulocyte colony-stimulating factormobilized peripheral blood mononuclear cell (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 48 publications
2
37
2
Order By: Relevance
“…As previously reported, 45 we also observed a significant advantage of high graft CD3 + cell dose with respect to OS, PFS and NRM, even after adjustment for pre-transplant ATG use. Interestingly, patients transplanted with high graft CD34…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 89%
See 1 more Smart Citation
“…As previously reported, 45 we also observed a significant advantage of high graft CD3 + cell dose with respect to OS, PFS and NRM, even after adjustment for pre-transplant ATG use. Interestingly, patients transplanted with high graft CD34…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 89%
“…44 We did not observe such a negative impact of very high dose (data not shown). As previously reported, 45 we also observed a significant advantage of high graft CD3 + cell dose with respect to OS, PFS and NRM, even after adjustment for pre-transplant ATG use. Interestingly, patients transplanted with high graft CD34 + or CD3 + cell doses did not experience higher risks for chronic GVHD.…”
supporting
confidence: 89%
“…Among T-cell subsets, both CD4 þ and CD8 þ T cells might promote T-cell engraftment, confirming previous observations in a canine model 15 and in patients given HCT after myeloablative 16,17 or nonmyeloablative conditioning. 18,19 Furthermore, since CD14 þ cells contained in G-PBMC grafts secrete large amounts of IL-10 (an immunosuppressive cytokine) and have reduced expression of costimulatory molecules needed for T-cell activation, those cells might provide immunosuppressive effects that reduce host-versus-graft (rejection) reactions. 20 The role of CD3 þ cells for the development of acute and chronic GVHD after allogeneic HCT has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al, using the same preparative regimen combining 2 Gy TBI with or without fludarabine, showed that higher numbers of transplanted CD8 þ T-cells correlated with increased donor T-cell chimerism levels on day 28 after HCT (P ¼ 0.009), and greater likelihood for achievement of full donor T-cell chimerism (P ¼ 0.03) in a study analyzing combined observations in 63 patients given PBSC from either related (n ¼ 38) or unrelated (n ¼ 25) donors. 59 Finally, we analyzed the impact of graft composition on HCT outcomes among 116 patients receiving PBSC from HLA-matched unrelated donors after conditioning with fludarabine and 2 Gy TBI. 60 High numbers of donor T-cells (P ¼ 0.03), CD4 þ T-cells (P ¼ 0.007), CD8 þ T-cells (P ¼ 0.29), NK cells (P ¼ 0.04) and CD34 þ progenitor cells (P ¼ 0.01) in the graft were each associated with high levels of day-28 donor T-cell chimerism.…”
Section: Factors Affecting Chimerism Levels After Reduced-intensity Omentioning
confidence: 99%